Meningkatkan Minat Hafalan Surah Pendek Siswa Sekolah Dasar Negeri Karangloe Melaui Kegiatan Pesantren Ramadhan Dalam Program Merdeka Belajar Kampus Merdeka - Yunus, Andi Ibrahim; Fatimah, Andi; Sompa, A. (LPPM UNIVERSITAS KHAIRUN, 2024)
Education is something that is very important for human life, both in terms of personal, family, community and state life. In fact, there are still many problems that must be faced in order to improve the quality of education in Indonesia, especially religious education. For students of SD Negeri Karangloe, it was found that there were only a few students who memorized short surah well and fluently according to the tajwid rules. The purpose of the community service activities carried out is to find out how the memorization method is carried out in accordance with the theory so that it increases interest in memorizing short surah so that it helps students memorize short surahs. This community service activity involved lecturers and teachers as resource persons, religious teachers as judges, students from several universities, staff and employees of SD Negeri Karangloe, as well as the Malakaji Village community who were directly involved and participated in this activity, and students as contest participants. The activities carried out include: preparatory meetings, preparation for activities, and the implementation of competitions. Based on the objectives of the community service activities carried out, it was found that the results of the implementation of the short surah memorization competition which were attended by school students needed to be planned and implemented annually, so that it could be developed into a verse and surah memorization competition of the Al-Quran so that students as tahfiz were able to compete starting from village level to national level.